2022
DOI: 10.3390/ijms232214443
|View full text |Cite
|
Sign up to set email alerts
|

The Crosstalk between HepG2 and HMC-III Cells: In Vitro Modulation of Gene Expression with Conditioned Media

Abstract: Epidemiological studies have postulated an inverse correlation between developing cancer and neurodegeneration. It is known that the secretome plays a vital role in cell–cell communication in health and disease; the microglia is the resident macrophage of the central nervous system which maintains neuronal integrity by adapting as the microenvironment changes. The present study aimed to identify, in a cell model, biomarkers that link neurodegenerative diseases to cancer or vice versa. Real-time PCR and western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…In this study, we chose to compare metabolic responses of conditioned media-treated cells with non-conditioned cells. This approach has previously been used to explore changes in, e.g., lipolysis and gene expression induced by conditioned medium given to the acceptor cells [30,31]. Another approach would be to use transwell co-cultures [32], allowing indirect cell-to-cell contact; however, due to different culturing conditions for growth and differentiation of myotubes and osteoblastic cells, this approach was difficult to implement.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we chose to compare metabolic responses of conditioned media-treated cells with non-conditioned cells. This approach has previously been used to explore changes in, e.g., lipolysis and gene expression induced by conditioned medium given to the acceptor cells [30,31]. Another approach would be to use transwell co-cultures [32], allowing indirect cell-to-cell contact; however, due to different culturing conditions for growth and differentiation of myotubes and osteoblastic cells, this approach was difficult to implement.…”
Section: Discussionmentioning
confidence: 99%
“…19 Likewise, an Italian research group found that the culture media of central nervous system resident macrophages (HMC-III cells) induce an autophagic process triggering, as well as cytoprotective effects on the HB cell line (Hep G2) against various pro-inflammatory and pro-oxidant factors. 20 Recently, bioinformatics-based HB studies shed more light on the involvement of TAMs in immune cell invasion. A single-cell RNA-seq analysis of genetic data from 13 treatment-naïve HB patients showed aberrant accumulation of erythroblastic islands (EIs), which restrain anti-tumor immunity and inversely correlate with survival.…”
Section: Protumor Phenotypes Of Tams In Hbmentioning
confidence: 99%
“…The aforementioned Italian research group also found that the culture media of Hep G2 cells induces the same cytoprotective effects on HMC-III cells. 20 Likewise, The HB cell secretome includes: HGFLP, 15 M-CSF, GM-CSF, 6 and IL-34, 13 known to chemoattract and stimulate TAMs. The secretome also includes: macrophage migration inhibitory factor (MIF), 23 OSM, 17 nitric oxide synthetase 2 (NOS2), 24 and IL-34, 13 found to induce protumor M2 macrophage polarization state.…”
Section: Protumor Phenotypes Of Tams In Hbmentioning
confidence: 99%
See 2 more Smart Citations